Applications of Nanotechnology-based Approaches to Overcome Multi-drug Resistance in Cancer - Kalave, Sana; Hegde, Namita; Juvale, Kapil (Current Pharmaceutical Design, 2022)
Cancer is one of the leading causes of death worldwide. Chemotherapy and radiation therapy are the major treatments used for the management of cancer. Multidrug resistance (MDR) is a major hindrance faced in the treatment of cancer and is also responsible for cancer relapse. To date, several studies have been carried out on strategies to overcome or reverse MDR in cancer. Unfortunately, the MDR reversing agents have been proven to have minimal clinical benefits, and eventually, no improvement has been made in therapeutic efficacy to date. Thus, several investigational studies have also focused on overcoming drug resistance rather than reversing the MDR. In this review, we focus primarily on nanoformulations regarded as a novel approach to overcome or bypass the MDR in cancer. The nanoformulation systems serve as an attractive strategy as these nanosized materials selectively get accumulated in tumor tissues, thereby improving the clinical outcomes of patients suffering from MDR cancer. In the current work, we present an overview of recent trends in the application of various nano-formulations, belonging to different mechanistic classes and functionalization like carbon nanotubes, carbon nanohorns, carbon nanospheres, liposomes, dendrimers, etc., to overcome MDR in cancer. A detailed overview of these techniques will help researchers in exploring the applicability of nanotechnologybased approaches to treat MDR.
Keywords: nanocarriers